Occurrence of salmonid alphavirus (SAV) and piscine orthoreovirus (PRV) infections in wild sea trout Salmo trutta in Norway - Madhun, AS; Isachsen, CH; Omdal, LM; Bårdsgjære Einen, AC; Bjørn, PA; Nilsen, R; Karlsbakk, E (Diseases of aquatic organisms, 2016)
Viral diseases represent a serious problem in Atlantic salmon (Salmo salar L.) farming in Norway. Pancreas disease (PD) caused by salmonid alphavirus (SAV) and heart and skeletal muscle inflammation (HSMI) caused by piscine orthoreovirus (PRV) are among the most frequently diagnosed viral diseases in recent years. The possible spread of viruses from salmon farms to wild fish is a major public concern. Sea trout S. trutta collected from the major farming areas along the Norwegian coast are likely to have been exposed to SAV and PRV from farms with disease outbreaks. We examined 843 sea trout from 4 counties in Norway for SAV and PRV infections. We did not detect SAV in any of the tested fish, although significant numbers of the trout were caught in areas with frequent PD outbreaks. Low levels of PRV were detected in 1.3% of the sea trout. PRV-infected sea trout were caught in both salmon farming and non-farming areas, so the occurrence of infections was not associated with farming intensity or HSMI cases. Our results suggest that SAV and PRV infections are uncommon in wild sea trout. Hence, we found no evidence that sea trout are at risk from SAV or PRV released from salmon farms.